The Influence of the Finished Goods Inventory Accounting Information System on Internal Control of Finished Goods Inventory: Study Of One of The Companies Providing Explosives and Mining Blasting Services in Indonesia - Ananda Hilda Fadillah; Indah Damayanti; Indri Ayu Tansar; Lungguh Jatmika (Majalah Bisnis & IPTEK, 2025)
This study aims to assess and analyze the impact of the Finished Goods Inventory Accounting Information System on the internal control of finished goods inventory at a company offering explosives and mining blasting services in Indonesia. Implementing an appropriate Finished Goods Inventory Accounting Information System and its practical utilization is anticipated to enhance the internal control of finished goods inventory inside the organization. The employed research method is descriptive verification, with data analyzed through simple linear regression to elucidate the relationship or influence between the two variables concerning a company that offers explosives and mining blasting services in Indonesia. To support this research, the author gathered secondary data using questionnaires from 35 employees at the company. The study's findings yield the linear regression equation Y = 10.891 + 0.777X, which indicates a significant favorable impact on Y. The Finished Goods Inventory Accounting Information System accounts for 65.7% of the Internal Control of Finished Goods Inventory in a company offering explosives and mining blasting services in Indonesia. In comparison, the remaining 34.3% is attributed to other unexamined variables.